Kartini’s Views on Opium Problems in Java at the End of the 19th Century - Abdul Wahid (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
In the 1890s, the discourse on the negative effects of opium consumption among Native people turned into a political movement, which demanded that the Dutch colonial government reform its policies on opium. In the same period, Raden Ajeng Kartini, a priyayi (noble) woman from Jepara, developed her intellectual capabilities and thinking. Her letters, it was later discovered, contained critical ideas concerning the disadvantaged position of Javanese women. In addition to this, as an issue attracting greater public scrutiny, the opium problem also drew Kartini’s attention, as evinced in at least two letters to Stella Zeehadnelaar and Mrs. Abendanon-Madri. Curiously, Kartini’s views on the opium problem have been given little scholarly attention in the rich literature on her life, with most scholarly work focusing on her “feminist” thoughts and ideas. For that reason, this article offers an analysis on this very specific aspect of Kartini’s thoughts, delving further into its historical context and what it means in terms of her existing historical persona.